Joint linkage and association mapping of preserved cognition in the old‐order Amish: Genetics/genetics of cognitive aging. (7th December 2020) - Ramos, Jairo; Jaworski, James; Adams, Larry D.; Laux, Renee A.; Caywood, Laura J.; Prough, Michael; Clouse, Jason E.; Herington, Sharlene D.; Slifer, Susan H.; Fuzzell, M. Denise; Fuzzell, Sarada L.; Sewell, Jane L.; et al.
Abstract: Background: Most studies on Alzheimer Disease (AD) have focused on the identification of variants associated with increased risk. The Amish is a genetically homogeneous population ideal to investigate susceptibility genes for complex traits such as AD. This study aims to use family‐based linkage and association approaches to identify genetic variants that protect against the development of cognitive impairment (CI), the central feature of AD. Method: A total of 800 adults from Amish communities in Indiana and Ohio were screened for CI using the 3MS test. Individuals were classified as cognitively normal (CN) if the 3MS score was ≥87 at age 75 and cognitively impaired if < 87 at any age. Samples were genotyped on the Illumina Infinium Global Screening or Expanded Multi‐Ethnic Genotyping Array. Over 7 Million common and rare variants were then imputed using the HRC reference panel. For the linkage analysis 75 nuclear families containing at least two CN individuals were analyzed using Merlin to fit multipoint non‐parametric linkage models and parametric affected‐only (AO) dominant and recessive models using a map of more than 40, 000 genotyped markers. The genome‐wide association study (GWAS) of imputed variants utilized the program Genesis to fit a logistic regression model 426 CN to 360 CI, associating each variant with cognitive status while adjusting for sex, pc1, pc2 and relatedness. Result: The top linkage peaks were seen in the parametric multipoint AO dominant model: Chr3 (HLOD = 2.6) ∼3.9 mb region (21.0 mb – 24.9 mb) and Chr11 (HLOD 2.1) ∼6.5 mb (11.0 mb – 17.5 mb). In the GWAS analysis, no variants reached genome wide significance (5 × 10 −8 ). However, using a lower significance threshold for regional association under a linkage peak (p < 10 −5 ), 7 associated variants were identified in two regions under the Chr11 peak. Conclusion: We identified a 6.5 mb area of interest on chromosome 11 associated with preserved cognitive function in Amish adults over age 75, which is near OTOG a previously reported gene associated with AD. This region merits further investigation for functional variants that might slow or prevent the development of cognitive impairment in older adults.